Affordances of short video platforms and SME digital communication innovation: the mediating role of the innovation-decision process - Rozaq, Miftahul; Dianita, Indria Angga; Wisudawaty, Hanna; Adim, Adrio Kusmareza (Frontiers in Communication, 2025)
Short video platforms such as TikTok, Instagram Reels, and YouTube Shorts have quickly become central to digital communication strategies, particularly for micro, small, and medium enterprises (MSMEs). Compared with previous social media platforms, short video platforms possess unique affordances, such as visibility, virality, multimodal expression, and low-cost experimentation, enabling MSMEs to innovate in digital communication. Although prior research has extensively examined the adoption of short video platforms, the specific mechanisms by which these affordances shape the innovation-decision processes of MSMEs are still rarely explored. This study formalizes the short video platforms affordance of digital communication innovation pathways through innovation-decision process, bridging affordance theory with UTAUT2 and diffusion of innovation perspectives, thereby extending social media innovation literature in the MSMEs context. The research method used survey data from MSMEs in Bandung Regency, Indonesia, using Likert-scale measurements on 392 MSMEs and SEM-PLS analysis. The findings suggest that short video platforms have a positive impact on digital communication innovation, with the innovation-decision process serving as a partial mediator (VAF ≈ 38%). Theoretically, this study integrates the affordances theory with UTAUT2 and extends the adoption model by showing how short video platform affordances activate utilitarian, social, and hedonic factors that shape the innovation-decision process.